The Relationship Between Employment Status And Mother's Nutrition Patterns In Exclusive Feeding In Mangunsari Village Lumajang District - Remita Ayu Agustin; Candra Wahyuni (Master of Public Health Program Universitas STRADA Indonesia, 2021)
Breast-feeding to newborns is one of the efforts to prevent death and undernourishment problems in infants and toddlers, about 15% of the total incidence of children under five years of age in developing countries asa result of exclusive breast-feeding. Exclusive breast milk that is given to infants for up to 6 months is not added to other foods such as formula, lemon, honey, tea, water, bananas, milk porridge, cookies, and other foods. Infants who are exclusively breast-fed can avoid diseases. Sick infants are given exclusively by breast feeding can accelerate. This journal's search process electronically and online using one database, which is googgle sholar from 2015-2020 . The inklational criteria of the journal have the same variable as research, the journal used is the journal's 30-200 Indonesian respondents. Based on the journals received results that from the six journals it is evident there is a link between work status and a nutrient pattern in exclusive breast-feeding. This is confirmed by prior research. Thus, mother's work and nutritional patterns influence exclusive breast-feeding.